The Challenges of the Competencies Model of Teacher Training: Examples from Chile - Espinoza, Oscar; González, Luis Eduardo; Sandoval, Luis; McGinn, Noel; Corradi, Bruno (Journal of Education and Training, 2022)
This paper reports on a qualitative evaluation of the conceptual coherence of current programs of teacher training in three Chilean universities. Influenced by the Bologna Accord’s emphasis on development of competencies, the national government recently called for a shift from teaching as transmission of disciplinary-based cognitive knowledge to a transdisciplinary development of cognitive and non-cognitive skills in knowledge production. The paper, based on narrative analysis, is the first assessment of how three universities have responded to the new approach. Intensive interviews with teacher training program directors asked about goals, decision criteria, and methods of assessing impact on teacher trainees. The most selective university is using formal mechanisms to validate trainees’ attainment of specified competencies. In the middle and less selective universities less attention is paid to internal validation and programs rely on informal assessment mechanisms not always consistent with quality assurance requirements. The paper concludes that all three universities are guided more by labor market demands and employability of their graduates than by educational theory or research on teaching practices.